Induction by caterpillars of stored and emitted volatiles in terpene chemotypes from populations of wild cotton (Gossypium hirsutum) - Marine Mamin; Mary V. Clancy; Galien Flückiger; Teresa Quijano-Medina; Biiniza Pérez-Niño; Luis Abdala-Roberts; Ted C. J. Turlings; Carlos Bustos-Segura (BMC Plant Biology)
Abstract Background Upland cotton (Gossypium hirsutum) plants constitutively store volatile terpenes in their leaves, which are steadily emitted at low levels. Herbivory leads to a greater release of these stored volatiles. Additionally, damaged plants increase the accumulation of volatile terpenes in their leaves and begin to synthesize and emit other terpenes and additional compounds. This has been well characterised for cultivated G. hirsutum, but little is known about volatile production in response to herbivory in wild populations. We investigated how damage by a generalist herbivore species, the beet armyworm (Spodoptera exigua), affects leaf-stored and emitted volatiles in wild G. hirsutum plants and compared the responses of two known chemotypes. Wild cotton plants were grown in a greenhouse from seeds collected from four distinct locations covering sixteen populations, along the Yucatan coast (Mexico), from where this cotton species originates. We assessed whether the differences in leaf terpene profiles between the two chemotypes persisted upon herbivory, in leaves and in headspace emissions, and whether these chemotypes also differed in the production and release of herbivory-induced volatiles. In addition to chemotypic variation, we further investigated intraspecific variation in the volatile response to herbivory among genotypes, populations, and the four geographic regions. Results The difference between the two chemotypes persisted after herbivory in the stored volatile profile of induced leaves, as well as in the emissions from damaged plants. Therefore, wild cotton chemotypes may differ in their airborne interactions with their environment. The specific terpenes distinguishing these chemotypes showed a weak inducibility, raising questions about their functions. Herbivory triggered changes in stored and emitted volatiles similar to what is known for cultivated varieties of G. hirsutum. However, we report for the first time on the emission of volatile aldoximes by cotton plants, which were only detected in the headspace upon herbivory, and displayed chemotypic and interpopulation variation. Intraspecific variation was also observed in the induced emissions of nitriles and certain terpenes. Moreover, chemotypes differed in their induction of (E)-β-ocimene stored in the leaves. Conclusions This comprehensive insight into herbivore-induced volatiles of wild cotton reveals variation in production and emission among populations. A full understanding of their ecological role may help in the development of future pest-management strategies for cotton crops.